TEACHING AND LEARNING DURING COVID19 CRISIS : CHALLENGES, OPPORTUNITIES AND THE WAY FORWARD - Rusli, Ahmad; Luqman Hakim, Satiman; Hana, Hamidi (PERKAMA INTERNATIONAL PERSATUAN KAUNSELING MALAYSIA ANTARABANGSA, 2022)
The COVID-19 pandemic as a big crisis in quarter one of 21century has created unprecedented challenges to the all sectors of life. The COVID-19 pandemic has exposed gaps in the digital infrastructure and network performance as internet usage rises. In the education sector, the closure of many educational institutions had resulted in the disruption of face-to-face learning which significantly impacted the majority of students. While it is obvious that online learning provides many advantages like easy access, unlimited access to resources, flexibility in learning and easy collaboration, lack of infrastructure had caused a serious setback to the core principles of traditional pedagogy such as learner interaction, access to study materials, attentional skills, regularity, time management, and assessment. Although online learning faces many issues and challenges among stakeholders, especially students and educators, it also serves as a great alternative for the spread of knowledge and represents a significant benefit when distance is no longer a barrier. COVID-19 pandemic in particular has brought online learning to a new level where its adoption within the education world was not an optional but mandatory for the survival of our new generation.